Investigating the implementation of continuous assessment by grade 7 Social Studies teachers in the Oshana education region - Matheus, Hilya (Rhodes University, Faculty of Education, Department of Education, 2007)
Since independence in 1990, Namibia's Ministry of Education Sport and Culture has focused on curriculum and assessment reforms. The introduction of Continuous Assessment (CA) for appraising learners' achievement was considered to be a very important aspect of teaching and learning. This study focused on the implementation of CA in schools. The study explores how the selected grade 7 Social Studies teachers understand and implement CA. This study was conducted in the Oshana region of Namibia. Four grade 7 Social Studies teachers participated from two different schools. This study was done through a case study to gain insight into the implementation of CA in schools. Semi-structured interviews, observations and document analysis were the research methods used to collect the data. The findings indicate that these teachers have a theoretical understanding of what CA implies and what role it plays and are aware of assessment strategies. However these theoretical perspectives are not translated into practice. This implies a limited understanding of CA and reflects a gap between the teachers' theoretical understanding of CA and its practical implementation. The study also identified various systemic factors that hamper the implementation of CA, which include overcrowded classrooms, increased teachers' workload by CA, shortages of resources such as textbooks and lack of professional development. The nature of pre-service teacher education the participants went through, professional development programmes that are given to teachers as in-service training and a lack of guidelines in the syllabus on how to approach continuous assessment are clearly evident in the findings as factors that contribute to the teachers' gap between theory and practice. The study concludes that even though a number of workshops on continuous assessment were conducted, the teachers still could not implement it as expected. The study findings inform my professional context as an Advisory Teacher and that of my colleagues. Therefore it made me realize what the teachers' needs are and what kind of support they require.
Keywords: Educational tests and measurements -- Namibia; Social sciences -- Study and teaching (Elementary) -- Namibia